A graphical method for membrane penetration in triaxial tests on granular soils - Mohd. Jamaludin, Md. Noor, Dr.; Nyuin, Joe Davylyn; Adnan, Derahman, Engr. Dr. (The Institution of Engineers, Malaysia (IEM), 2013)
Link to publisher's homepage at http://www.myiem.org.my/